Educação, turismo e hotelaria: percepções dos egressos do curso de hotelaria da universidade federal do maranhão sobre sua formação e o mercado de trabalho - Jonilson Costa Correia (2018)
This study had the objective of analyzing the perceptions that graduates of the Hotel Course of the Federal University of Maranhão on their training and the labor market. Because it is a research aimed at the graduates of a single institution, it was necessary to approach it historically, enabling a contextual view of the course researched from Education, Tourism and Work theories. I have taken as a theoretical reference in the construction of this research object the studies of Frigotto (2003, 2004), Mészáros (2016), Morin (2010, 2016), Bourdieu (1983), Kuenzer (1997; 2001) Pochmann (2012) among others, which allowed to understand and interpret this phenomenon. For the accomplishment of the research, I opted for the qualitative approach using semi-structured interview as data collection technique. The analysis of the data was made from the qualitative model through the analysis of oral narratives from where I was able to capture from the subjects' speeches of their experiences, subjectivities, emotions, dreams and expectations, as well as the contradictions interconnected to the context in the trajectories of the graduates from their formation to the insertion in the labor market from their narratives means talking about different times, sources and places of the course, the challenges and perspectives of the training in this area, it also means evaluating their history, the curricular components of the course and the teaching work. The subjects involved in the survey were the graduates of the UFMA (Bachelor's Degree) in Hospitality, graduated in different years. In order to select the subjects investigated, I used the following criteria: the graduates of the course that work in several hotel sectors, hospital, restaurants, hotel and tourism teaching, enology and hotel management. Along the categories of analysis and narratives of the interviewees, I have perceived fragilities, contradictions and mainly gaps that need to be filled, spaces that need to be revisited by teachers, students and the hotel and tourism school of UFMA in its various extension and research projects and during the classroom activities. I think that only in this way can there be a permanent dialogue between academia and the labor market. It is necessary to go beyond the walls of the school and to know or recognize that the knowledges are plural and therefore come from various sources